ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH DILIHAT DARI RASIO DERAJAT DESENTRALISASI FISKAL, RASIO KEMANDIRIAN KEUANGAN DAERAH DAN RASIO EFEKTIFITAS: West Lampung Regency Government for Fiscal Year 2021-2022 - Rini Utari; Anisa Nursyabani; Hurun In; Royke Bahagia Rizka; Sandy Kurniawan (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2023)
Abstrak The purpose of this study is to evaluate the financial performance of West Lampung Regency, the regional government. A quantitative descriptive approach is the research methodology employed. The budget for regional revenue in 2021 and 2022 is the data that was used. Analysis of the regional financial independence ratio, effectiveness ratio, and degree of fiscal decentralization ratio was the calculation method employed in the study. The degree of fiscal decentralization as a ratio is very low, with analysis results ranging from 0% to 10% on an interval scale. When the independence ratio falls between 0 and 25 percent, it indicates a very low level and an instructive relationship pattern. Lastly, an interval scale with x>100% represents the effectiveness ratio in 2021. Keywords: Financial Performance; Effectiveness Ratio; Degree of Fiscal Decentralization Ratio; and Regional Financial Independence Ratio